Conceptualization, measurement and effects of positional issues in the Canadian electoral context. Issue 4 (April 2019) - Dufresne, Yannick; Ouellet, Catherine
Abstract: It is a well-known fact that the major Canadian political parties now use political marketing tools to segment the electorate and target specific groups of voters. Positional issues are at the centre of this type of micro-targeting strategy. This article demonstrates that positional issues played a greater role in Canadian electoral politics than previously assumed. Despite the many theoretical reasons for why the effects of positional issues might have been overlooked, accounting for disaggregation error shows stable and consistent effect of positional issues on vote choice in Canada. Multi-item issue scales are used to test the stability and relative strength of positional issues compared to rival concepts, such as values and party identification. Once measured through aggregated items, the effects of positional issues on vote choice in Canada might even compare with those of conventional vote predictors, such as party identification. Hence, it shows that the actions parties take to capitalize on positional issues, as described by the political marketing literature, are justified.